A link that matters: towards phenomenological tests of unimodular asymptotic safety - Brito, Gustavo Pazzini de; Eichhorn, Astrid; Duarte Pereira Junior, Antônio (Journal of high energy physics, 2019)
Constraining quantum gravity from observations is a challenge. We expand on the idea that the interplay of quantum gravity with matter could be key to meeting this challenge. Thus, we set out to confront different potential candidates for quantum gravity - unimodular asymptotic safety, Weyl-squared gravity and asymptotically safe gravity — with constraints arising from demanding an ultraviolet complete Standard Model. Specifically, we show that within approximations, demanding that quantum gravity solves the Landau-pole problems in Abelian gauge couplings and Yukawa couplings strongly constrains the viable gravitational parameter space. In the case of Weyl-squared gravity with a dimensionless gravitational coupling, we also investigate whether the gravitational contribution to beta functions in the matter sector calculated from functional Renormalization Group techniques is universal, by studying the dependence on the regulator, metric field parameterization and choice of gauge.
Gesehen am 23.12.2019